Cidade Velha e Feliz Lusitânia: cenários do Patrimônio Cultural em Belém - MIRANDA, Cybelle Salvador (Universidade Federal do Pará, 2011)
The Thesis was motivated by the rediscovery of Cidade Velhas district, in Belém, state of Pará, rediscovered by the authors childhood and the district as a memory space and landmarks for the risorgimento of Pará state. Analyze the concepts of patrimony in modern city, as though the mythic imaginary which lives in the citizens memory in tree stages: Pombal Colonization; the Belle Èpoque and the New Pará. The argumentation is constructed by actors narratives such as: old residents, new residents, business men, patrimony technician, so by the images reading which help to tell the districts history and to tell how is it saw as a heritage. The ethnographic method and the semiotic were the reading guides for the written spoken and visual materials, helping to the researchers position as an older habitant, architect and plastic artist. Drawing a map with the culture concepts in the Cidade Velhas district, since the residents point of view to the planers of Feliz Lusitânia Project, this work is as open view of the theme heritage in Cidade Velha, which revels contradiction between the definition of patrimony of the patrimony technician and the social groups.